Genetic diversity of porcine circoviruses 2 and 3 circulating among wild boars in the Moscow Region of Russia - Krasnikov, Nikita; Rykova, Valentina; Kucheruk, Oksana; Komina, Alina; Pchelnikov, Alexander; Gulyukin, Alexey; Yuzhakov, Anton (Frontiers in Veterinary Science, 2024)
Porcine circoviruses (PCV) are widely distributed in swine herds. PCV2, the significant swine pathogen, causes infections characterized by growth and development disorders, skin lesions, and respiratory distress. PCV3 has been circulating worldwide and can be associated with various clinical signs and disease developments. Wild boars are the main reservoir of these pathogens in wildlife and can create an alarming threat to pig farming. In Russia, three PCV2 genotypes (PCV2a, PCV2b, and PCV2d) were identified in pig farms. Additionally, PCV3 was observed in pig herds during the monitoring studies in the country. However, data considering the circulation of PCVs in herds of wild boars in Russia is scant. For this purpose, we performed PCR assays of the samples from 30 wild boars hunted in the Moscow Region of Russia in 2021-2023. The ratios of wild boars positive for PCV2, PCV3, or coinfected were 50%, 10%, and 13.3%, respectively. Additionally, we sequenced 15 PCV2 and four PCV3 complete genomes and conducted phylogenetic analysis, which divided PCV2 isolates into two groups: PCV2d and PCV2b. The study showed a high infection rate of PCV2 among wild boars, with PCV2d dominance. Simultaneously, PCV3 also circulates among wild boars. The obtained results can provide a basis for the development of preventive measures to support infection transmission risks between farm and wild animals.